Incidence Rate of Hypersensitivity Reactions to Bee-Venom Acupuncture - Lee, Eun-Jung; Ahn, Yo-Chan; Kim, Young-Il; Oh, Min-Seok; Park, Yang-Chun; Son, Chang-Gue (Frontiers in Pharmacology, 2020)
Introduction: Bee-venom acupuncture (BVA) has been widely applied to various disorders including pain-related diseases; however, patients are often warned of adverse reactions such as anaphylaxis. This study aimed to estimate the risk of hypersensitivity reactions to BVA and to determine their clinical features. Methods: We retrospectively surveyed the medical records of patients treated by BVA between January 2010 and April 2019 in Dunsan Hospital of Daejeon University, and all cases of allergic reactions and their clinical symptoms were analyzed. Results: A total of 8,580 patients (males 4,081 and females 4,499) were treated with BVA which amounts to a total of 60,654 treatments (average 7.1 ± 14.8 times). A total of fifteen patients (7 males and 8 females) reported an allergic reaction (0.175%, 95% CI 0.086 ~ 0.263) of type 1 hypersensitivity, indicating a rate of allergic reaction in 0.025% (95% CI 0.012 ~ 0.037) of the total BVA treatments. The average number of BVA treatments in those patients was 6.9 ± 6.5 (males 4.1 ± 3.4 and females 9.3 ± 7.9). Among the cases of hypersensitivity reactions, 4 involved anaphylactic shock; therefore, the incidence rate of anaphylaxis was 0.047% (95% CI 0.001 ~ 0.092) for the 8,580 subjects and 0.007% (95% CI 0.000 ~ 0.013) for the 60,654 treatments. All grade 1 cases were recovered within 1 day, whereas others took up to 30 days for complete recovery. Conclusion: Our results may emphasize paying attention to unforeseeable risks of anaphylaxis after bee-venom acupuncture. This study could be essential reference data for the guidelines of appropriate use of bee-venom acupuncture and bee-venom-derived interventions in clinical applications.